How and why instructors use open access lessons - Noyes, Keenan; Treibergs, Kira; Burbach, Sara M.; Stetzer, MacKenzie R.; Smith, Michelle K.; Couch, Brian A. (Frontiers in Education, 2024)
IntroductionOpen educational resources (OERs) provide instructors access to no-cost lesson materials they can incorporate into their courses. OER lessons can promote the use of innovative and evidence-based educational practices in biology education. Prior research suggests that teaching strategies are often implemented in different ways which can impact student learning. However, few studies have explored how OER lessons are modified to fit their local context.MethodsWe used the teacher-curriculum framework to understand how and why instructors modify these materials. Additionally, we explored how these materials supported instructors in enacting national priorities from Vision and Change. We surveyed 139 instructors who implemented lessons published in CourseSource, a peer-reviewed journal specifically designed to share OERs.ResultsWe found that the majority of instructors who used the lesson materials (e.g., slides, worksheets, assessments, protocols) did so without making substantial modifications, in contrast with prior research. Furthermore, we found that these materials were particularly helpful in incorporating student-centered teaching practices, like group work or discussions, sometimes for the first time.DiscussionThese insights into what instructors value in lesson materials can inform OER publishing guidelines so that these materials best meet instructional needs.